Damped Zigzag Upward Motion of a Ball in Fluid: a Numerical Model - Muhammad Nur Tajuddin; Novitrianc Novitrianc; Sparisoma Viridi; Euis Sustini; Veinardi Suendo (Institut Teknologi Bandung, 2009)
Several types of upward motion of a ball in a cylinder filled with water are observed in experiment such as straight, damped zigzag, and zigzag upward motion. Center of mass of the balls and the way the balls are released play important role to determine the type of occuring upward motion. A simple theoretical model regarding only gravitational force, Stokes drag force, and Archimedes bouyancy force, where the work points of these forces are not coincident, are developed and used to explain the damped zigzag motion.